Simulation and Optimization of Digital Circuits Considering and Mitigating Destabilizing Factors - Melikyan, Vazgen (Springer International Publishing, 2018)
This book describes new, fuzzy logic-based mathematical apparatus, which enable readers to work with continuous variables, while implementing whole circuit simulations with speed, similar to gate-level simulators and accuracy, similar to circuit-level simulators. The author demonstrates newly developed principles of digital integrated circuit simulation and optimization that take into consideration various external and internal destabilizing factors, influencing the operation of digital ICs. The discussion includes factors including radiation, ambient temperature, electromagnetic fields, and climatic conditions, as well as non-ideality of interconnects and power rails. Discusses the construction of a new class of simulators that takes into account various internal and external destabilizing effects on the operation of digital integrated circuits; Includes detailed explanation of key topics, including models, algorithms, and characteristics of software development; Focuses on issues pertaining currently to development of real integrated circuits.